THEOLOGY AFTER CHRISTENDOM forming prophets for a post-christian world. - Searle, Joshua T. ([S.l.] : CASCADE BOOKS, 2018)
Christianity must be understood not as a religion of private salvation, but as a gospel movement of universal compassion, which transforms the world in the power of God's truth. Amid several major global crises, including the rise of terrorism and religious fundamentalism and a sudden resurgence of political extremism, Christians must now face up fearlessly to the challenges of living in a "post-truth" age in which deceitful politicians present their media-spun fabrications as "alternative facts." This book is an attempt to enact a transformative theology for these changing times that will equip the global Christian community to take a stand for the gospel in an age of cultural despair and moral fragmentation. The emerging post-Christendom era calls for a new vision of Christianity that has come of age and connects with the spiritual crisis of our times. In helping to make this vision a reality, Searle insists that theology is not merely an academic discipline, but a transformative enterprise that changes the world. Theology is to be experienced not just behind a desk, in an armchair, or in a church, but also in hospitals, in foodbanks, in workplaces, and on the streets. Theology is to be lived as well as read.
Includes bibliographical references.
Master record variable field(s) change: 050, 072, 082, 650
Keywords: Theology -- Forecasting; Theology -- History; Christianity -- Forecasting; RELIGION / Christian Church / History; RELIGION / Christianity / History; Electronic books